V-Locate: Development of Web-Based Vulcanizing Shop Locator for 2nd District of Oriental Mindoro - Melendres, Uriel M.; Balboa, Marlon D.; Clementer, Mariel G. (International Journal of Computing Sciences Research, 2022)
Purpose –When traveling, getting a punctured tire is a common and inevitable problem that makes a vulcanizing shop business in demand in the province. Vulcanizing shop repairs flat tires and sells a typical car and motorcycle needs. However, this small business was not tagged in the known navigation application. Thus, the proponents conceptualized a Web-based application locating the nearest vulcanizing shops and motorcycle spare parts stores. The V-locate will not just provide the nearest shops and stores but also the information like the offered products and services. The scope of the map on the said application is only limited to the areas within the 2 nd District of Oriental Mindoro. Method –The methodology used in development is Rapid Application Development (RAD), suitable for creating active phase software applications. To get the exact coordinates of every vulcanizing shop and spare parts store, the proponents used Geographical Positioning System (GPS) application. Several scripting languages, such as PHP and JavaScript, and their framework and library, are used to develop the app. Results – The system was evaluated by 60 respondents consisting of faculty, drivers, and Rider's Club members conforming to ISO 25010 software quality standards. The evaluation result got 4.4 for functional suitability, 4.4 for usability, 4.5 for security, and 4.3 for Performance Efficiency, which shows that the system is efficient and feasible for implementation. Conclusion –The vulcanizing shop in a province like Oriental Mindoro is of great help to travelers when they meet unexpected emergencies like having a flat tire. With that said, the development of the V-Locate application is essential for travelers in case they encounter such a mishap. Recommendations – For further improvement of the system, it is recommended to conduct beta testing and another evaluation using the remaining criteria of ISO 25010. Also, it is crucial to widen the scope of the map and make it offline. Research Implications –Once the system is fully implemented, it will ease the burden of travelers in Oriental Mindoro to find repair shops in case of an emergency. Moreover, it also promotes and recognizes the existence of vulcanizing shops as a local business in the province.